Pengaruh Implementasi Marketing Mix Terhadap Keputusan Pembelian Pada Supermarket Tokomu Kotagajah - Muslikah, Putri; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of the implementation of the marketing mix on purchasing decisions at the TOKOMU Supermarket in Gajah City. This type of research is an explanatory research that explains the causal relationship (cause and effect) between the variables that affect the hypothesis. This study discusses the influence of the marketing mix on purchasing decisions consisting of product, price, promotion, and place variables. Data obtained from observations and questionnaires given to 60 respondents. The analytical technique used is the Instrument Requirements Test, Classical Assumption Test and Hypothesis Testing. The results of this study indicate that product, price, promotion, and place variables have a positive and significant influence on purchasing decisions. Keywords: Product, Price, Promotion, Place, Purchase Decision.